Assessment of scenarios for the development of the digital economy in Ukraine - Gren, Roman (Global Prosperity, 2023)
This article is dedicated to the development of the digital economy as a key factor in ensuring a country's innovation security. The article discusses the development of a scenario approach to the development of the digital economy, which involves the following stages: identifying key factors in the development of the digital economy, their interdependence, and possible development options; identifying possible development scenarios depending on changes in key factors; forming the main scenarios for the development of the digital economy and conducting their analysis. When identifying possible scenarios for development, two key factors were highlighted: «business interest in the implementation of digital technologies and readiness to invest in digital transformation» and «state policy in supporting the digital economy». A «scenario grid» was constructed that involves combining different variants of the combination of these factors. Four possible scenarios for the development of the digital economy in Ukraine were formulated: optimistic (active state participation in promoting the spread of digital technologies), conservative (state funding for fundamental research and business funding for digital technologies), moderately optimistic (business actively investing in digital technologies, and the state not playing a decisive role), and pessimistic (the state minimizes its role in promoting the development of the digital economy, and businesses finance the production of traditional products). The post-war recovery of Ukraine's economy should be based on the development of the innovation sector and the spread of digital technologies. In the absence of a strategy for ensuring innovation security based on the development of the digital economy, there is a high probability of implementing a conservative scenario for the development of the digital economy.